Influence of Personal Hygiene on Stunting Occurrence - Nuraina, Nuraina; Malia, Anna; Raudhati, Sri (Universitas Teuku Umar, 2023)
Stunting is a significant problem that Indonesia must overcome to produce an excellent cognitive and physical development generation. Stunting is a problem in Bireuen Regency, Indonesia, and must be managed because it has long-term impacts on the future generation. According to data from the World Health Organization (WHO), in 2017, Indonesia had the third-highest stunting prevalence rate globally, at 32.6%. Even though the stunting prevalence rate in Indonesia decreased from 37.2% in 2013 to 27.7% in 2018, it is still far from the WHO target of not exceeding 20%. Therefore, the government is making efforts to rates s rate e reduce the prevalence of stunting in Indonesia by issuing The Regulation of the Republic of Indonesia’s President Number 72 the Year 2021 about the acceleration of stunting decrease. Based on the result of a nutrition case study of Indonesia in 2021, Aceh’s stunting rate reached 33,18% until it was included among the seven provinces with the highest stunting cases in Indonesia. One of the regencies in Aceh Province that needs immediate solutions to solve stunting is Bireuen Regency. The purpose of this research was to find out the influence of personal hygiene on stunting occurrence. The study used an analytical, quantitative method with a cross-sectional approach. This method aims to analyse the impact of personal hygiene on stunting occurrence in Pandrah Sub District Bireuen Regency. The sample selection technique in this research was the entire population, namely 62 people. Based on the research conducted in Pandrah Sub District, Bireuen Regency, the research results showed that personal hygiene had a significant influence on stunting occurrence, with a p-value of 0.001 (which is less than the significance level of 0.05). It could be concluded that personal hygiene significantly influences stunting occurrence.